Effects of palm oil fuel ash and crumb rubber on mechanical and thermal properties of sustainable engineered cementitious composites - Rahman M.H.; Kong S.Y.; Lam B.Y.B.; Murali G.; Wong L.S.; Paul S.C. (Elsevier Ltd, 2025)
The construction sector using natural sand causes rapid depletion and environmental harm, including erosion, biodiversity loss, and aquatic habitat destruction. To address these challenges and advance sustainability, this study systematically investigated the behaviour of engineered cementitious composites (ECC) incorporating 10?30 % ground palm oil fuel ash (GPOFA) and crumb rubber (CR) as a fine aggregate substitution. Two different sizes of GPOFA, P600 (in the range of 300 ?m?600 ?m) and P300 (less than 300 ?m), were utilized to substitute the fine aggregate in the mix. Dry density, workability, thermal conductivity, modulus of elasticity, tensile strength and strain, compressive strength, flexural strength, and ultrasonic pulse velocity (UPV) were investigated. Furthermore, the microstructures and mineralogical compositions of the selected ECC samples were also examined. The results indicate that increasing GPOFA and CR content reduced ECC's flowability and density. Incorporating GPOFA reduced the compressive strength by 23 % for P600, 12 % for P300, and 74 % for CR, for 30 % substitution at 28 days. Both substitutions reduced the modulus of elasticity and UPV of ECC due to reduced packing efficiency and increased porosity. Increasing GPOFA improved the first cracking load slightly but decreased ultimate flexural strength, whereas CR significantly reduced both. In addition, tensile strain and strength dropped more significantly for ECC with CR compared to ECC with GPOFA. ECC with CR recorded the highest shrinkage and the lowest thermal conductivity (0.66W/mK). Overall, P600 outperformed P300, and CR showed the lowest performance in ECC across all parameters studied. This study highlights that partial replacement of silica sand with GPOFA could produce greener ECC with acceptable mechanical properties, while CR effectively reduces the thermal conductivity of ECC. Integrating GPOFA and CR adds significant value to these wastes while simultaneously providing a sustainable solution for waste disposal. ? 2024 Elsevier Ltd